Descriptive Analysis of Assesment Practices in ELT: Teacher’s Perspectives and Challenges - Nuha, Muhammad Ulin; Irmayani, Irmayani (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study looks at how English language teaching (ELT) teachers see evaluation processes and points out the challenges they run across when bringing them to pass. A mixed-methods approach was applied to interview a large sample of English teachers from various educational environments both qualitatively and statistically. The results reveal a strong inclination for formative assessment strategies that increase student participation and provide instantaneous feedback, such tests and peer review. Conversely, summative assessments—which resemble high-stakes tests—are sometimes viewed as demanding and as inaccurate of a reflection of students' actual abilities. This paper emphasizes major challenges to individualized feedback and inventive assessment strategies including time constraints, large class numbers, and pressure from standardized testing. The lack of opportunities for evaluation literacy professional development presented still another major challenge. Although technology integration in evaluations is thought to increase participation, it also raises questions regarding data protection and fair access. These findings underline the need of a comprehensive evaluation plan that honors formative activities and meets criteria for summative evaluation. Examined are recommendations for improved professional development and educational policy in order to support effective assessment strategies.